(untitled) (Journal of the College of Basic Education, 2019)
Zinc Oxide (ZnO) thin films were prepared on glass subsetrate at a temperature of 673 K using the Chemical Spray Pyrolysis (CSP) technique and annealed at (723 and 773) K for 120 minutes. The results show that the absorbance and coefficient of absorption decreases with the high temperature of annealing, the band gap of direct transition and the index of refraction increases with higher annealing temperature as the photon energy increases within the range that is visible. The high infrared transmittance increases with the temperature of higher annealing. The value of the peak for all optical properties excluding transmittance shift / decrease. Results agree that thin film (723 and 773) K is appropriate as photocatalytic material